2015
DOI: 10.1007/s10826-015-0121-y
|View full text |Cite
|
Sign up to set email alerts
|

Resources, Exposure to Trauma, and the Behavioral Health of Youth Receiving Public System Services

Abstract: Using Conservation of Resources Theory (COR), the current study examined the relationship between exposure to trauma, resources, and behavioral health in a prospective longitudinal cohort of youth in a public behavioral health system. The sample includes 303 youth, aged 5-19, who had received 6 months of treatment-asusual in an urban, diverse public behavioral health system, and who had experienced at least one type of trauma. Youth entered treatment with an average of four types of trauma and five accessible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…What has been examined in the literature are protective factors that may mediate against the negative effects of ACEs. Studies have suggested that, compared to those with fewer advantages, individuals with a greater number of identified and developed advantages, especially interpersonal strengths, tend to have fewer behavioral health problems ( Accomazzo, Israel, & Romney, 2015 ; Whitson, Bernard, & Kaufman, 2013 ). As an important part of interpersonal relationship, peer relationship have been addressed in existing studies to have a significant impact on the emotional and behavioral development of people, and positive relationship may play an important role in moderating the negative effects of ACEs.…”
Section: Introductionmentioning
confidence: 99%
“…What has been examined in the literature are protective factors that may mediate against the negative effects of ACEs. Studies have suggested that, compared to those with fewer advantages, individuals with a greater number of identified and developed advantages, especially interpersonal strengths, tend to have fewer behavioral health problems ( Accomazzo, Israel, & Romney, 2015 ; Whitson, Bernard, & Kaufman, 2013 ). As an important part of interpersonal relationship, peer relationship have been addressed in existing studies to have a significant impact on the emotional and behavioral development of people, and positive relationship may play an important role in moderating the negative effects of ACEs.…”
Section: Introductionmentioning
confidence: 99%